2015
DOI: 10.1182/blood-2014-12-614677
|View full text |Cite
|
Sign up to set email alerts
|

VPS33B regulates protein sorting into and maturation of α-granule progenitor organelles in mouse megakaryocytes

Abstract: Key Points• Hematologic effects in the mouse model for ARC syndrome, Vps33b fl/fl -ER T2, in which Vps33b is ubiquitously excised post-development.• The VPS33B-VIPAR complex is responsible for sorting cargo to and maturation of a-granule-destined MVBs.Arthrogryposis, renal dysfunction, and cholestasis (ARC) syndrome is caused by deficiencies in the trafficking proteins VPS33B or VIPAR, and is associated with a bleeding diathesis and a marked reduction in platelet a-granules. We generated a tamoxifen-inducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 42 publications
2
71
0
Order By: Relevance
“…Under steady-state conditions VPS33B and VIPAR do not significantly localize to LE (22), but we have shown that these proteins can be recruited to LE by RILP (30). In line with a function of VPS33B and VIPAR at the LE, it was recently shown that VPS33B is important for the maturation of the ␣-granule, a specialized late endosomal compartment (34). Therefore, we investigated whether pathogenic mutations in VPS33B could still be recruited to LE by RILP.…”
Section: Arc Mutations Specifically Disrupt Vps33b-vipas39 Interactiomentioning
confidence: 95%
“…Under steady-state conditions VPS33B and VIPAR do not significantly localize to LE (22), but we have shown that these proteins can be recruited to LE by RILP (30). In line with a function of VPS33B and VIPAR at the LE, it was recently shown that VPS33B is important for the maturation of the ␣-granule, a specialized late endosomal compartment (34). Therefore, we investigated whether pathogenic mutations in VPS33B could still be recruited to LE by RILP.…”
Section: Arc Mutations Specifically Disrupt Vps33b-vipas39 Interactiomentioning
confidence: 95%
“…It is caused by mutations in VPS33B or VIPAS39; genes that encode two vesicle-mediated protein-sorting proteins (VPS33B and VIPAR) that form a functional complex. Studies on MKs in a conditional mouse model of ARC syndrome have confirmed abnormalities in protein trafficking from the trans Golgi network or via endocytosis and in the maturation of multivesicular bodies, a subset of late endosomes and precursors of agranules [21]. Only a restricted population of small a-granule-like structures is present in platelets from ARC patients and, distinctively, P-selectin is severely decreased.…”
Section: Gray Platelet Syndrome and The Nbeal2 Genementioning
confidence: 96%
“…To determine potential molecules that play important roles in exosome secretion, we screened several potential candidates that previous studies have suggested may participate in vesicle trafficking, including VPS16B, VPS33B, RAB11A, and RAB27A (22,27,29,33). We found that VPS16B and VPS33B, but not RAB11A or RAB27A (Supplemental Figure 1D), were highly enriched in human plasma-derived exosomes ( Figure 1F).…”
Section: Introductionmentioning
confidence: 98%
“…We found that VPS16B and VPS33B, but not RAB11A or RAB27A (Supplemental Figure 1D), were highly enriched in human plasma-derived exosomes ( Figure 1F). Because VPS33B has been reported to be a regulator of MVB maturation (22,27,28), we speculated that secretory proteins may be associated with VPS33B. Therefore, we examined the colocalization of VPS33B and several groups of candidate proteins known to be critical for HSC stemness (TPO, ANGPTL2, ANGPTL3, LDHA, and PKM2) (8,14,15,34,35) as well as other potential HSC stemness regulators (GLUT1 and other members of the ANGPTL family) (34,36) using immunofluorescence staining.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation